2x+1.22014 = 22015.
4 + 22 + 23 + 24 + … + 22015 = 2x
tìm x:
2x + 1 . 22014= 22015
\(2^{x+1}\cdot2^{2014}=2^{2015}\\ 2^{x+1}=2^{2015}:2^{2014}\\ 2^{x+1}=2\\ =>x+1=1\\ x=1-1\\ x=0\)
Bài 27. Tìm x biết
a. 89 – (73 – x) = 20 b. (x + 7) – 25 = 13 c. 98 – (x + 4) = 20
d. 140 : (x – 8) = 7 e. 4(x + 41) = 400 f. x – [ 42 + (–28)] = –8
g. x + 5 = 20 – (12 – 7) h. (x – 11) = 2.2³ + 20 : 5 i. 4(x – 3) = 7² – 1³.
j. 2x+1.22014 = 22015. k. 2x – 49 = 5.3² ℓ. 3²(x + 14) – 5² = 5.2²
m. 6x + x = 511 : 59 + 31. n. 7x – x = 521 : 519 + 3.2² – 70.
o. 7x – 2x = 617 : 615 + 44 : 11. p. 3x = 9 q. 4x = 64
r. 9x–1 = 9 s. x4 = 16 t. 2x : 25 = 1
u. |x – 2| = 0 v. |x – 5| = 7 – (–3) w. |x – 5| = |–7|
x. |x| – 5 = 3 y. 15 – 2|x| = 13
a) 89-(73-x) = 20
=> 73+x =89-20
=> 73+x=69
=> x=69-73
=> x=-4
b) (x+7)-25=13
=> x+7=13+25
=> x+7=38
=> x=38-7
=> x=31
c) 98-(x+4)=20
=> x+4=98-20
=> x+4=78
=> x=78-4
=> x=73
d) 140:(x-8)=7
=> x-8=140:7
=> x-8=20
=> x=20+8
=> x=28
e) 4(x+41)=400
=> x+41=400:4
=> x+41=100
=> x=100-41
=> x=59
f) x-[42+(-28)]=-8
=> x-14=-8
=> x=-8+14
=> x=6
g) x+5=20-(12-7)
=> x+5=20-5
=> x+5=15
=> x=15-5
=> x=10
h) \(x-11=2.2^3+20:5\)
=> x-11=2.8+4
=> x-11=16+4
=> x-11=20
=> x=20+11
=> x=31
i) \(4\left(x-3\right)=7^2-1^3\)
=> 4(x-3)=49-1
=> 4(x-3)=48
=> x-3=48:4
=> x-3=12
=> x=12+3
=> x=15
a) 5x – 65 = 5.32
b) 200 – (2x + 6) = 43
c) 2(x−51) = 2.23 + 20
d) 135 – 5(x + 4) = 35
e) (2x – 4)(15 – 3x) = 0
f) 2x+1.22014 = 22016
g) 15+(x−1)3=42
h)15 – x = 17+ (−9)
i) | x − 5| = |−7|+(−4)
k) | x − 3| − 12= −9+ | −7|
a) \(5x-65=5.3^2 \\ 5x-65=45\\5x=45+65\\5x=110\\x=22\)
b) \(200-(2x+6)=4^3\\2x+6=200-4^3\\2x+6=136\\2x=130\\x=65\)
c) \(2(x-51)=2.2^3+20\\2(x-51)=16+20\\2(x-51)=36\\x-51=18\\x=51+18=69\)
d) \(135-5(x+4)=35\\5(x+4)=135-45\\5(x-4)=90\\x-4=18\\x=18+4=22\)
e) \((2x-4)(15-3x)=0\\2(x-2).3(5-x)=0\\(x-2)(5-x)=0\\ \left[ \begin{array}{l}x-2=0\\5-x=0\end{array} \right. \\ \left[ \begin{array}{l}x=2\\x=5\end{array} \right.\)
f) \(2^{x+1} . 2^{2014}=2^{2016} \\ (2^{x+1} . 2^{2014}):2^{2014}=2^{2016} :2^{2014} \\ 2^{x=1}=2^{2016-2014} \\2^{x+1}=2^2\\x+1=2\\x=1\)
g) \(15+(x-1)^3=43\\(x-1)^3=15-42\\(x-1)^3=-27\\(x-1)^3=(-3)^3\\x-1=-3\\x=-2\)
h) \(15-x=17+(-9)\\15-x=17-9\\15-x=8\\x=15-8\\x=7\)
i) \(|x-5|=|-7|+|-4|\\|x-5|=7+4\\|x-5|=11\\ \left[ \begin{array}{l}x-5=11\\x-5=-11\end{array} \right. \\ \left[ \begin{array}{l}x=16\\x=-6\end{array} \right.\)
k) \(|x-3|-12=-9+|-7|\\|x-3|-12=-9+7\\|x-3|-12=-2\\|x-3|=10 \\ \left[ \begin{array}{l}x-3=10\\x-3=-10\end{array} \right. \\ \left[ \begin{array}{l}x=13\\x=-7\end{array} \right.\)
c) 2 2016 . 2 x - 1 = 2 2015
c) 2 2016 . 2 x - 1 = 2 2015
2 x - 1 = 2 2015 : 2 2016
2 x - 1 = 2 2015 - 2016
2 x - 1 = 2 - 1
⇒ x – 1 = -1
x = -1 + 1
x = 0
A = 1 + 21 + 22 + ... + 22015
\(A=1+2^1+2^2+...+2^{2015}\)
\(2\cdot A=2^1+2^2+2^3+...+2^{2015}+2^{2016}\)
\(2A-A=2^1+2^2+2^3+...+2^{2015}+2^{2016}-\left(1+2^1+2^2+...+2^{2015}\right)\)
\(A=2^{2016}-1\)
B = 22018 - 22017 - 22016 - 22015 - 22014
\(B=2^{2018}-2^{2017}-2^{2016}-2^{2015}-2^{2014}\)
\(=>2B=2^{2019}-2^{2018}-2^{2017}-2^{2016}-2^{2015}\)
\(=>2B+B=2^{2019}-2^{2014}\)
\(=>B=\dfrac{2^{2019}-2^{2014}}{3}\)
A=22015*72020 nhan 1 bieu thuc
Tính tổng: A = 1+21 + 22 + 23 + 24 + .... + 22015
`#3107`
\(A=1+2^1+2^2+2^3+...+2^{2015}\)
\(2A=2+2^2+2^3+2^4+...+2^{2016}\)
\(2A-A=\left(2+2^2+2^3+2^4+...+2^{2016}\right)-\left(1+2+2^2+2^3+...+2^{2015}\right)\)
\(A=2+2^2+2^3+2^4+...+2^{2016}-1-2-2^2-2^3-...-2^{2015}\)
\(A=2^{2016}-1\)
Vậy, \(A=2^{2016}-1.\)
\(A=2^0+2^1+2^2+...+2^{2015}\)
\(2\cdot A=2^1+2^2+2^3+...+2^{2016}\)
\(A=2A-A=2^{2016}-2^0\)
\(A=2^{2016}-1\)